(untitled) (Veterinary Science Development, 2015)
Negative energy balance can impair the metabolism of high producing dairy cows and supplying the glucose, as an energy source; can prevent the metabolic disorders in these animals. Hence, we hypothesized that bolus intravenous glucose administration may change the concentrations of metabolic hormones in order to prevent and control of metabolic dysfunctions of dairy cows. Twenty five multiparous Holstein dairy cows were divided to 5 equal groups containing early, mid and late lactations, far-off and close-up dry periods. All cows were received dextrose 50% intravenously at 500 mg/kg, 10 mL/kg/h. Blood samples were collected from all animals prior to and 1, 2, 3 and 4 after dextrose 50% infusion and sera were separated to determine glucose, triiodothyronine (T3), thyroxine (T4), serum free T3 (fT3), free T4 (fT4), cortisol and insulin like growth factor-1 (IGF-1). The decreasing pattern of T3 concentration was detected in all studied animals following intravenous glucose infusion (P<0.05). The significant increasing pattern of T4 levels was seen in early and mid lactation cows after glucose administration (P<0.05). The significant decreasing pattern of IGF-1 was detected in mid and late lactations and far-off dry groups (P<0.05). There were no significant alterations in fT3, fT4 and cortisol concentrations following glucose infusion in all experimental groups. In conclusion, bolus intravenous glucose infusion could influence the metabolic hormones in high producing Holstein dairy cows. Alterations of metabolic hormones following bolus intravenous glucose administration indicated that glucose is an important direct controller of metabolic interactions and responses in dairy cows during different physiological states.